ANALISIS PENGARUH LOVE OF MONEY TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Pradanti, Noviani Rindar; Prastiwi, Andri (Diponegoro Journal of Accounting, 2014)
This research is the development of previous study conducted by Elias (2010) by adding two dependent variable which art social economic status and ethnic background. This study aims to analize correlation between gender, education level, social economic status, and ethnic background to the accounting students ethical perception thought love of money as intervening variable.The sample in this study were taken by using the data collection method called convinience sampling. The sample of this research are undergraduated accounting students, PPA and master of accounting students of University of Diponegoro. The number of sample that used were 60 respondens. The data obtained were analyzed by using PLS analysis technique (Partial Least Square) through PLS software.The result showed of the research shows that gender influences accounting students ethical perception but not has to effect with love of money. While education level, social economic status, ethnic background variable has no effect towards love of money. Love of money as intervening variable influences accounting students ethical perception.